Karakteristik komposit bio-foam pati-glukomanan pada variasi formulasi perbandingan foaming agent natrium bikarbonat dengan asam sitrat - I Wayan Arnata; Early Dea Kartika Fiano; I Gusti Ayu Lani Triani (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Styrofoam food packaging has many advantages. However, it has been reported to be hazardous to health and the environment, so it is necessary to develop bi-foam as a safe packaging alternative. This research aims to determine the effect of variations in the formulation ratio of foaming agents based on sodium bicarbonate (NaHCO3) and citric acid (CA) on the starch-glucomannan bio-foam characteristics and to determine the appropriate comparison formulation to produce the best bio-foam characteristics. This research used a randomized block design with treatment formulation variations of NaHCO3 and CA ratio, consisting of 5 levels, namely 8:4, 8.5:3.5, 9:3, 9.5:2.5, and 10:2. Each treatment was grouped into three so that 15 experimental units were obtained. The variables observed were density, tensile strength, compressive strength, water adsorption capacity, and functional groups by Fourier-Transform Infrared Spectroscopy (FTIR), surface morphology by Scanning Electron Microscope (SEM), and thermal stability by Thermogravimetric Analyzers/ Differential Thermogravimetric (TGA/DTG). The research results showed that the foaming agent formulation from NaHCO3/CA significantly affected the density, tensile strength, compressive strength, and water adsorption capacity of the starch-glucomannan bio-foam. Bio-foam with a NaHCO3/CA ratio of 8:4 has the properties of low water adsorption capacity, high tensile strength, and compressive strength but has the disadvantage of a relatively high-density value. The NaHCO3/CA (8:4) produces the best characteristics with a density of 0.36 g/cm3, water adsorption capacity of 2.95%, tensile strength of 0.22 MPa, and compressive strength of 1.48 MPa. FTIR analysis shows changes in the spectral intensity of the functional groups of the bio-foam polymer as an indication that interaction has occurred between the functional groups of each polymer. SEM analysis shows that bio-foam, adding a NaHCO3/CA, produces a relatively rougher and more porous surface. At the same time, its thermal stability is lower than that of bio-foam without adding a foaming agent.